New financial technologies, sustainable development, and the international monetary system - Eswar S. Prasad (Asian Development Bank Institute (ADBI), 2021)
New financial technologies - including those underpinning cryptocurrencies - herald broader access to the financial system, quicker and more easily verifiable settlement of transactions and payments, and lower transaction costs. Domestic and cross-border payment systems are on the threshold of transformation, with significant gains in speed and lowering of transaction costs on the horizon. For emerging market and developing economies, the digitization of finance carries a number of potential benefits, including broadening of financial inclusion, quicker and cheaper cross-border remittances, and increased convenience of domestic payments. But some of these developments could also increase these countries' exposure to volatile capital flows. Governments, central banks, and regulatory agencies will face difficult challenges in striking the right balance between fostering innovations and mitigating risks arising from them.
Keywords: G0; E5; 330; fintech; payment systems; international payments; financial inclusion; capital flows; financial regulation